CREATING AN IMMORTAL BODY IN THE EXTERNAL VOID: THE ALCHEMICAL WAY OF WANG DONGTING 汪東亭 (1839–1917) - Mozias, Ilia (Journal of Chinese Religions, 2023)
This paper explores the teachings of Wang Dongting ??? (1839–1917), a leading master of the Western school (xipai ??) of internal alchemy (neidan ??), who developed an innovative method of alchemical cultivation that focused on creating the immortal body in the external space outside of the physical body. Wang developed a concept of two Heavens and four yin-yangs, presenting the perfect immortal and corrupted ordinary worlds as two parallel universes existing simultaneously. The two Heavens express themselves as humans’ two selves, an ordinary self and its physical body given to us by our parents, and the eternal “body of law.” Wang maintained that alchemists must abandon the ordinary self and exclusively cultivate the body of law, achieving immortality by separating the body of law from the physical body and “teaching” the latter to exist on its own. According to Wang’s method, alchemists form a new immortal body by unifying their genuine selves with external space. To do it, practitioners first focus on breathing outside the physical body, then naturally follow breathing, then forget about it and go into deep concentration, oblivion, and even sleep. They finally awaken in an actual dream of this new immortal reality. Practitioners not only create a new immortal body outside the physical one, but also make a choice between the ordinary world of death and the immortal world of life, aiming to leave our fallen world entirely, forget about it, and never return.
Created from Fastlane, Scopus look-up
Keywords: immortality; internal alchemy; the body of law; Wang Dongting; Western school

Immortals and Alchemists: Spirit-Writing and Self-Cultivation in Ming Daoism - Mozias, Ilia (Journal of Daoist Studies, 2018)
What role do immortals play in the life and practice of a community of alchemists? In this paper, I examine the role of immortals in the cultivation practice of a small alchemical community formed around the famous Ming alchemist Lu Xixing. Lu and his companions had no connection to any religious institution, and instead of looking for a human master, they turned to the practice of spirit-writing. In séances, they met numerous immortals and discussed with them various aspects of self-cultivation and personal life. Lu collected detailed records of these conversations in his key treatise, which documents how immortals became members of their community and transformed alchemical cultivation into a journey in the twilight zone between the human and immortal worlds. They accompanied Lu and his companions on all stages of alchemical cultivation and helped them enter a state of mind necessary for achieving enlightenment. Participation in spirit-writing séances allowed the Daoists to practice internal alchemy without leaving their habitual literati life.<br